The Abandoned Settlements of Cyprus Under Immediate Threat Due to Climate Change: : A Case Study of the Fοinikas Settlement in Paphos - Vergas, Georgios; Chatzigiannopoulos, Themistoklis (Technical Annals, 2025)
The island of Cyprus is home to many settlements that have remained frozen in time, standing as silent witnesses to a turbulent past. Their abandonment resulted from various political, social, economic, and geomorphological factors. Yet, these traditional settlements now confront a new, pressing challenge: the climate crisis. Desertification, shifting rainfall patterns, and rising temperatures accelerate the deterioration of the built environment, erasing tangible traces of history. The gradual disappearance of these settlements underscores the urgent need for strategies to protect and manage cultural heritage in the face of new environmental challenges. This study focuses on the abandoned settlement of Foinikas in the Paphos district, chosen as a case study due to the temporal and spatial dynamics of the interaction between water bodies and settlements. The abandoned village lies on the northwestern shore of Asprokremmos, Cyprus’s second-largest natural water reservoir. The dynamic impact of water has altered the settlement’s footprint, submerging entire sections, while exposure to climatic conditions gradually erodes the traces of memory. The study demonstrates that unless solutions are found to mitigate climate-related threats, Foinikas is expected to become a mere memory. The research proposes the revitalization of the settlement through the creation of an experiential sugar production museum, leveraging the settlement’s historical connection to water and its ties to sugar production. The design integrates local and cultural assets with innovative architectural solutions, proposing a dynamic model of sustainability and resilience in response to environmental challenges. This study advances an innovative strategy for preserving cultural heritage, ensuring historical continuity and resilience against climate threats and natural hazards.